Expected Value of Control and the Motivational Control of Habitual Action - Eder, Andreas B.; Dignath, David (Frontiers in Psychology, 2019)
A hallmark of habitual actions is that, once they are established, they become insensitive to changes in the values of action outcomes. In this article, we review empirical research that examined effects of posttraining changes in outcome values in Pavlovian-to-instrumental transfer (PIT) tasks. This review suggests that cue-instigated action tendencies in these tasks are not affected by weak and/or incomplete revaluation procedures (e.g., selective satiety) and substantially disrupted by a strong and complete devaluation of reinforcers. In a second part, we discuss two alternative models of a motivational control of habitual action: a default-interventionist framework and expected value of control theory. It is argued that the default-interventionist framework cannot solve the problem of an infinite regress (i.e., what controls the controller?). In contrast, expected value of control can explain control of habitual actions with local computations and feedback loops without (implicit) references to control homunculi. It is argued that insensitivity to changes in action outcomes is not an intrinsic design feature of habits but, rather, a function of the cognitive system that controls habitual action tendencies.